Bifurcation analysis of commensalism intraction and harvisting on food chain model - Jawad, Shireen; Kazim Hassan, Sarab (Brazilian Journal of Biometrics, 2023)
In this paper, we study the incorporation of the commensalism interaction and harvesting on the Lotka–Volterra food chain model. The system provides one commensal prey, one harvested prey, and two predators. A set of preliminary results in local bifurcation analysis around each equilibrium point for the proposed model is discussed, such as saddle-node, transcritical and pitchfork. Some numerical analysis to confirm the accruing of local bifurcation is illustrated. To back up the conclusions of the mathematical study, a numerical simulation of the model is carried out with the help of the MATLAB program. It can be concluded that the system's coexistence can be achieved as long as the harvesting rate on the second prey population is lower than its intrinsic growth rate. Further, the role of mutual interaction can lead to the stability of the proposed system.